Impact of Healthcare Provider Awareness and Guidance on the Medical Cannabis Experience - Thomas A. Clobes; Marshall M. Mee; Jenna M. Jimenez; Jesus Maldonado; Joshua R. Song (Medical Cannabis and Cannabinoids)
Introduction: Cannabis as a therapeutic agent is accessible to a growing number of people, though research suggests that many medical cannabis (MC) users undertake their cannabinoid therapy independently, without collaborating with a cannabis clinician or informing their primary care provider (PCP). The effects of medical collaboration or disclosure to PCP on outcomes of cannabinoid therapy are unknown. Researchers anticipate that those who collaborate with a cannabis clinician or disclose their medical cannabis use to their PCP will find MC to be more effective, use less delta-9-tetrahydrocannabinol (THC) and more cannabidiol (CBD), and experience fewer side effects. Methods: Through an online survey, medical cannabis users reported their cannabis usage patterns, health outcomes, PCP awareness, and collaboration with cannabis clinicians. These responses were analyzed using a variety of statistical tests to search for differences in reported efficacy, specific cannabinoid, and side effects between different levels of medical professional involvement (n = 988). Results: Patients who either worked with a cannabis clinician or reported their use of their PCP reported significantly higher efficacy (p < 0.001), and in the case of working specifically with a cannabis clinician, higher daily doses of cannabidiol were used (p < 0.001). CBD doses did not vary between those who had disclosed their MC use to their PCP and those who had not. There were no significant differences in THC doses or side effects identified between groups. Conclusion: The results indicated that undertaking cannabinoid therapy with PCP awareness or guidance from a cannabis clinician is associated with better outcomes.